STUDIES ON THE NUTRITION OF HEMOPHILUS INFLUENZAE : I. THE RELATIONSHIP BETWEEN THE UTILIZATION OF COENZYME AND HEMIN AND THE REDUCTION OF NITRATE - Hoagland, Charles L. (The Rockefeller University Press, 1942)
The metabolic activity of H. influenzae can be followed quantitatively by measurement of the nitrite produced in a medium containing 0.2 per cent potassium or sodium nitrate. When X-factor, or hemin, and other specific substances required for the optimum growth of H. influenzae, are present in excess, the nitrite produced by this organism is quantitatively related to the concentration of V-factor, or total coenzyme. This quantitative relationship has been demonstrated for five strains of H. influenzae. It has been shown that various media, which in the past have been used for the determination of coenzyme by growth of H. influenzae, have in many instances been deficient in X-factor and that this substance rather than coenzyme has been the specific factor limiting growth. When 0.5 per cent blood is added to a basal proteose-peptone medium the specific requirements for optimum growth and metabolic activity of H. influenzae, other than coenzyme, are met, and a large number of specific biocatalysts and nutritive substances added to this medium are without effect in stimulating further growth. The foregoing studies have formed the basis for a quantitative method for the determination of total coenzyme in blood and tissue. This method is being described elsewhere.